Hubungan Pengetahuan dan Status Gizi Yang Mempengaruhi Kejadian Menarche Pada Remaja Putri di MTS Al-Mawahib Banjarmasin - Nisa Rahmadayanti; Novita Dewi Iswandari; Luthfia Hidayati Rahman; Dwi Sogi Sri Redjeki (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The first occurrence of menstruation, known as menarche, marks the onset of puberty in adolescent girls. The age at which menarche occurs is influenced by various factors, including knowledge and nutritional status. A lack of understanding about bodily changes during puberty may lead to unpreparedness for menarche, while poor nutritional status (underweight or overweight) can accelerate or delay its onset.This study aims to determine the relationship between knowledge and nutritional status with the incidence of menarche among female students at MTs Al-Mawahib Banjarmasin.This research used an analytical observational method with a cross-sectional approach. The sample consisted of 60 female students selected using total sampling technique. Data collection was conducted using a questionnaire and nutritional status was assessed using BMI . Data analysis used the Fisher’s Exact Test.Most respondents had poor knowledge, with 43 respondents (71.7%), and a normal nutritional status of 42 respondents (70.0%). The results of the Fisher’s Exact Test showed a significant relationship between knowledge and the incidence of menarche (p = 0.000), and also between nutritional status and the incidence of menarche (p = 0.003).There is a significant relationship between knowledge and nutritional status with the incidence of menarche among female students at MTs Al-Mawahib Banjarmasin.Schools are expected to provide education on reproductive health and nutrition to famale students.